Análise microbiológica da água procedente dos bombeamentos que abastecem o município de Parintins – Amazonas - Galúcio, Vanessa Costa Alves (2012)
Water is essential for life, but may present risks to the human health if engaged to low quality. In emerging countries, where can be found densely populated urban areas with inadequate sanitation system, water is responsible for a great number of waterborne diseases. Parintins – AM, is an island surrounded by Amazon River and about 400 km distant from Manaus. Parintins is the second Amazonian countryside city and presents substantial development on different sectors as economy, education and is specially known as the principal countryside tourist hub, indicating the need for more improvement on basic services for the population, mainly the service of water treatment. However, the population consumes underground water and the city does not have a station for water treatment. Therefore, this work aimed to analyze the microbiological quality of the water supplied from the water pumps to the population of Parintins. To achieve these objectives, water samples were collected weekly during January to September of 2011, and evaluated through the technique of filter membrane to detect the presence of coliforms bacteria and evolved forms of protozoa and helminthes, as well as the influence of river seasonality to the sanitary water quality. The results were compared with the values indicated by the 518/04 Ordinance of the Ministry of Health. The analyses results differs from those required by law, since shows the presence of coliform bacteria, like the faecal type, on water from the pumps. Protozoa and helminths were not detected and the river seasonality showed low influence to the quality of water distributed to Parintins. This work showed the need for corrective measures to ensure the quality of drinking water in Parintins – AM, as the construction of a treatment station for water and waste also present a plan for public awareness, with the government action. Keywords: Water Quality, Groundwater, Microbiological Analysis, Parintins, Seasonality.